In Vivo Elongation Patterns of the Collateral Ligaments in Healthy Knees During Functional Activities. (1st September 2021) - Hosseini Nasab, S.H.; Smith, C.R.; Postolka, B.; Schütz, P.; List, R.; Taylor, W.R.
Abstract : Background: Improved knowledge of in vivo function of the collateral ligaments is essential for enhancing rehabilitation and guiding surgical reconstruction as well as soft-tissue balancing in total knee arthroplasty. The aim of this study was to quantify in vivo elongation patterns of the collateral ligaments throughout complete cycles of functional activities. Methods: Knee kinematics were measured using radiographic images captured with a mobile fluoroscope while healthy subjects performed level walking, downhill walking, and stair descent. The registered in vivo tibiofemoral kinematics were then used to drive subject-specific multibody knee models to track collateral ligament elongation. Results: The elongation patterns of the medial collateral ligament varied distinctly among its bundles, ranging from lengthening of the anterior fibers to shortening of the posterior bundle with increases in the knee flexion angle. The elongation patterns of the lateral collateral ligament varied considerably among subjects. It showed an average 4% shortening with increasing flexion until 60% to 70% of the gait cycle, and then recovered during the terminal-swing phase until reaching its reference length (defined at heel strike). Conclusions: The observed nonuniform elongation of the medial collateral ligament bundles suggests that single-bundle reconstruction techniques may not fully restore healthy ligament function. Moreover, the observed ligament elongation patterns indicate greater varus than valgus laxity in the loaded knee. Clinical Relevance: Through providing key knowledge about the in vivo elongation patterns of the collateral ligaments throughout complete cycles of functional activities, this study offers in vivo evidence for benchmarking ligament reconstruction and soft-tissue balancing in total knee arthroplasty.